Fungsi Manajerial Kepala Sekolah Dalam Meningkatkan Kualitas Layanan Akademik di Sekolah Dasar - Aisfebrianty Aisfebrianty; Sitti Habibah; Sumarlin Mus (Universitas Negeri Makassar, 2023)
The purpose of this study is to determine the managerial function of the principal starting from school planning in order to improve the quality of the school, especially in academic services. This research research approach is qualitative with a type of research description. Data collection techniques include interviews, observations, and documentation. Data analysis techniques using the Miles and Huberman model. Checking the validity of data using triangulation techniques. The results showed that: 1) School planning, especially in academic services, created an annual program based on the school's vision and mission to create a superior generation in noble piety, achievement and based on cultural values in accordance with religious teachings, 2) Managing national standards of education, having developed teaching materials, conducting creative, innovative learning, developing talent interests, and conducting IT training, 3) Supervision and Evaluation, monitoring, providing solutions directly and supervising, 4) Carrying out school leadership to build good communication with subordinates and involve in decision making and 5) Management information systems in order to achieve the teaching and learning process and educational goals by utilizing technological advances in order to support school information systems, so that the managerial functions of the principal have been realized in accordance with the RKAS. In the school, it's just that it still needs to be improved.